Concrete with nanomaterials and fibers for self-monitoring of strain and cracking subjected to flexure - Ding, Y. (2018)
The nano-carbon black (NCB) and conductive fibers were added as multiple conductive materials to produce the electric conductive and ductile concrete. The effect of the NCB, CF and SF on the workability of fresh concrete was analyzed, the relationships between the FCR and the strain of initial geometrical neutral axis (IGNA) were established, and the self-sensing ability to the load-deflection process and cracking behavior of triphasic conductive concrete beam subjected to bending were investigated. The relationship between the fractional change in surface resistance (FCR) and the crack opening displacement (COD) of conductive concrete beams has been established. The results showed that the relationship between the FCR and the IGNA strain can be described by the First Order Exponential Decay function, and the slope of this function can reflect the sensitivity of the conductive concrete. A linearly correlation between FCR and COD was observed.